Dialectical encounters : contemporary Turkish Muslim thought in dialogue - Wilkinson, Taraneh R. (Edinburgh University Press, 2019)
Discussions of Islam in Turkey are still heavily dominated by political considerations and the dualistic paradigms of modern v. traditional, secular v. religious. Yet there exists a body of Muslim institutions in the country - Turkish theology faculties - whose work overcomes ideological divisions. By engaging with Turkish theology in its theological rather than political concerns, this book sheds light on complex Muslim voices in the context of a largely Western and Christian modernity. Featuring the work of Recep Alpyagil and Saban Ali D zg n, this innovative study provides a concise survey of Turkish Muslim positions on religious pluralism and atheism as well as detailed treatments of both critical and appreciative Turkish Muslim perspectives on Western Christianity. The result is a critical reframing of the category of modernity through the responses of Turkish theologians to the Western intellectual tradition.